Acridone alkaloids from the stem bark of Citrus aurantium display selective cytotoxicity against breast, liver, lung and prostate human carcinoma cells. (5th December 2018) - Segun, Peter A.; Ismail, Fyaz M.D.; Ogbole, Omonike O.; Nahar, Lutfun; Evans, Andrew R.; Ajaiyeoba, Edith O.; Sarker, Satyajit D.
Abstract: Ethnopharmacological relevance: Citrus aurantium L. (Rutaceae) is used, either singly or as a part of a polyherbal preparation, in Nigerian traditional medicine for the management of cancer and inflammatory diseases. Currently, there is a dearth of knowledge demonstrating its anticancer potential. Aim of the study: This study was carried out to determine the in vitro cytotoxicity of the crude extract of the stem bark of C. aurantium, identify and isolate the bioactive constituents and to establish the cytotoxicity of such constituents. Materials and methods: The powdered bark of C. aurantium was extracted by MeOH at room temperature (25–34 °C) and the crude extract was partitioned successively, with n -hexane, dichloromethane and methanol. Amongst the fractions, the DCM fraction was the most active and compounds were isolated from this fraction using a combination of chromatographic techniques. The structures of the isolated compounds were elucidated by spectroscopic means (MS, 1D and 2D NMR). The cytotoxicity of the extract, and the isolated compounds were evaluated by the MTT assay against four human cancer cell lines: A549 (lung), HepG2 (liver), MCF7 (breast) and PC3 (prostate). The selectivity of the isolated compounds was assessed using the normal human prostate epithelium cells (PNT2). Results and discussion: Of the three plant fractions, the DCM fraction showed significant cytotoxicity, with its highest activity against A549 cells (IC50 = 3.88 µg/mL) and the least activity on HepG2 cells (IC50 = 5.73 µg/mL). Six acridone alkaloids, citrusinine-I (1 ), citracridone-I (2 ), 5-hydroxynoracronycine (3 ), natsucitrine-I (4 ), glycofolinine (5 ) and citracridone-III (6 ), were isolated from the DCM fraction of C. aurantium. The isolated compounds demonstrated potent to moderate cytotoxicity (IC50 = 12.65–50.74 µM) against the cancer cells under investigation. It is noteworthy that the compounds exerted cytotoxicity at least four times more selective towards the carcinoma cells than the PNT2 cells. Conclusion: The results obtained from this study have provided some evidence for the ethnomedicinal use of C. aurantium against cancer and the acridone alkaloids present in its stem bark, have appeared to be responsible for the anticancer effects. Graphical abstract: